Comparison between carbonated and fruit-based soft drinks effect on calcium release from enamel surface of extracted permanent teeth - Siregar, Darmayanti; Nazriyanti, Gema; Fadhillah, Qanita (Padjadjaran Journal of Dentistry, 2022)
Introduction: People widely consume soft drinks due to their easy accessibility and delightful taste, without realising the impact on the tooth surface. Enamel dissolves easily due to acidic products that contact acid, a chemical demineralisation process (dental erosion). This study aimed to analyse the comparison between carbonated and fruit-based soft drinks effect on calcium release from enamel surface of extracted permanent teeth. Methods: In-vitro study with a time-series design was conducted on the population of extracted premolars taken from a private dental clinic and orthodontics clinic of the Faculty of Dentistry Universitas Sumatera Utara, Medan. The sample was obtained using the pairwise difference hypothesis test formula. The samples were 24 pieces divided into two treatment groups by immersing in carbonated drinks and fruit-based soft drinks for 5 to 60 minutes. The statistical test used was the independent t-test and generalised linear model-repeated measures (GLM-RM). Results: The calcium level after immersion in the carbonated drink at the fifth minute was 0.476±0.397 mg/L, then increased significantly at the sixtieth minute to 3.058±0.811 mg/L (p=0.001). In the fruit-based soft drinks immersion group, the dissolved calcium at the fifth minute was 0.671±0.208 mg/L, then increased significantly to 2.258±1.351 mg/L (p-value=0.028). Neither carbonated drinks nor fruit-based soft drinks showed a significant effect on the levels of dissolved calcium (p-value=0.135). Conclusion: In the fifth minutes of immersion, fruit-based soft drinks caused higher calcium release level compared to carbonated soft drinks. In contrast, in the sixtieth-minutes of immersion, the calcium release is found to be higher in the carbonated soft drinks group.